Fresno County Bar Association Legislators' Reception at The Downtown Club - Watkins, Howard::::::::: (1988)
State Assemblymember Bruce Bronzan and members of Fresno County Legal Secretaries: Linda Bankston, Mildren Christiansen, Jean Lewis, Qui Mei Christman, Bronzan, and Rhaelene Wimberly